show that limit x tends to (-infinity) (e^x - e^-x)/(e^x + e^-x) = -1

show that

limit x tends to  (-infinity)     (e^x - e^-x)/(e^x + e^-x) = -1


1 Answers

Sanjeev Malik IIT BHU
101 Points
12 years ago

f(x)= (ex-1/ex)/(ex+1/ex)

     =  (e2x-1)/(e2x+1)

and now simply put the value of .

see that x is negative so e2x will become 1/e2x(number)    here the value of x or number is infinity so will gaive infinite value at denominator . 1 diveded by by infinity is almost zero.

so limit becomes -1/1=  -1


please approve by clicking YES below

Think You Can Provide A Better Answer ?